Performance of FDG PET/CT in the clinical management of breast cancer - Groheux, David; Espié, Marc; Giacchetti, Sylvie; Hindié, Elif (Radiology, 2013)
In this analysis, the role of metabolic imaging with fluorine 18 fluorodeoxyglucose (FDG) in breast cancer is reviewed. The analysis was limited to recent works by using state-of-the-art positron emission tomography (PET)/computed tomography (CT) technology. The strengths and limitations of FDG PET/CT are examined in various clinical settings, and the following questions are answered: Is FDG PET/CT useful to differentiate malignant from benign breast lesions? Can FDG PET/CT replace sentinel node biopsy for axillary staging? What is the role of FDG PET/CT in initial staging of inflammatory or locally advanced breast cancer? What is the role of FDG PET/CT in initial staging of clinical stage IIA and IIB and primary operable stage IIIA breast cancer? How does FDG PET/CT compare with conventional techniques in the restaging of cancer in patients who are suspected of having disease recurrence? What is the role of FDG PET/CT in the assessment of early response to neoadjuvant therapy and of response to therapy for metastatic disease? Some recommendations for clinical practice are given.